Embolization for acute arterial bleeding: use of the triaxial system and N-butyl-2-cyanoacrylate. Issue 3 (1st March 2022) - Nakashima, Masahiro; Shimohira, Masashi; Nagai, Keiichi; Ohta, Kengo; Sawada, Yusuke; Ohba, Shota; Nakayama, Keita; Shibamoto, Yuta
Abstract: Purpose: The aim of this study was to evaluate the usefulness of transcatheter arterial embolization (TAE) using the triaxial system with N-butyl-2-cyanoacrylate (NBCA) for acute arterial bleeding in comparison to TAE using the triaxial system with gelatin sponges (GS) and/or coils. Material and methods: Between October 2013 and November 2018, 95 patients with acute arterial bleeding underwent emergency TAE using the triaxial system. Six patients underwent multiple TAEs and thus, 104 TAEs using the triaxial system were performed. In 26 of the 104 cases, TAE were performed with NBCA (NBCA group), and in the remaining 78 cases, TAE were performed with GS and/or coils (control group). Results: Hemorrhagic shock and coagulopathy more often occurred in the NBCA group. Procedure time was shorter in the NBCA group. The technical success rate was 100% in both groups ( p > 0.99). The clinical success rate in the NBCA and control groups was 92% and 96%, respectively ( p = 0.6). There was one minor complication (4%, 1/26) of liver dysfunction in a patient of the NBCA group, but no complication in the control group ( p = 0.26). Conclusion: TAE using the triaxial system with NBCA may be useful for acute arterial bleeding, especially in patients with hemorrhagic shock and coagulopathy.